Effect of Kinesiology Tape on Muscle Activation of Lower Extremity and Ankle Kinesthesia in Individuals With Unilateral Chronic Ankle Instability - Yin, Lulu; Liu, Kun; Liu, Chengmei; Feng, Xiaodong; Wang, Lin (Frontiers in Physiology, 2021)
Background: The purpose of the study was to determine the effect of kinesiology tape (KT) on lower limb muscle activation during computerised dynamic posturography (CDP) tasks and ankle kinaesthesia in individuals with chronic ankle instability (CAI). Methods: Thirty-five male participants with CAI participated in this study. The experimental procedure followed a repeated measures design. Muscle activation of lower extremity and ankle kinaesthesia of participants were measured using four taping treatments, namely KT, athletic tape (AT), sham tape (ST) and no tape (NT) in a randomised order. Muscle activation was assessed by surface electromyography (EMG) synchronised with CDP tests from seven lower extremity muscles of the unstable limb. Ankle kinaesthesia was measured by threshold to detect passive motion direction of the unstable ankle. Parameters were analysed by using one-way repeated measures ANOVA and followed by pairwise comparisons with a Bonferroni correction. Results: No significant difference was observed among different taping treatments for the majority of parameters during CDP. Except for condition 4 with open eyes, sway-referenced surface and fixed surround in the sensory organisation test (SOT), gastrocnemius medialis RMS was 28.19% lower in AT compared to NT (p = 0.021, 95% CI = 0.002 to 0.039) while gastrocnemius lateralis RMS was 20.25% lower in AT compared to KT (p = 0.038, 95% CI = 0.000 to 0.021). In forward-small sudden translation from motor control test (MCT), for peroneal longus, RMS was 24.04% lower in KT compared to ST (p = 0.036, 95% CI=0.000 to 0.018). In toes-down sudden rotation from adaption test (ADT), for peroneal longus, RMS was 23.41% lower in AT compared with ST (p = 0.015, 95% CI = 0.002 to 0.027). In addition, no significant difference was observed for threshold to detection of passive motion direction among different taping treatments. Conclusion: This research indicated that KT had minimal effect on muscle activation of unstable lower limb during static stance, self-initiated and externally triggered perturbation tasks from CDP and ankle kinaethesia among individuals with CAI, suggesting that the benefit of KT was too small to be clinically worthwhile during application for chronic ankle instability.